The costs of socializing with government officials: A new measure of corporate political connections - Jingjing Li; Liming Zhao (China Journal of Accounting Research, 2015)
We construct a new measure to capture corporate political connections, which is based on the amount a corporation spends on socializing with government officials. We examine the validity of this measure using the exogenous turnover of top local officials and find that firms increase their political networking expenditures when top local officials are replaced. Compared to state-owned enterprises (SOEs), non-state-owned enterprises (non-SOEs) react more aggressively to changes in local officials, which implies that non-SOEs have stronger incentives to build political connections with officials through social intercourse. We also find that firms located in regions with low levels of marketization react more aggressively to the turnover of local politicians. In addition, we find a positive effect of corporate political socializing expenditures on corporate performance and valuation, which suggests that political connections built through social intercourse benefit corporations.
Keywords: 650; Political connections; Turnover of officials; Political networking expenditures